Mérito no discurso pedagógico: Entre a força e o esforço - Tavares Mendes, Maíra (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This paper aims to discuss the notion of merit in pedagogical discourse. To do so, we present our presuppositions: historical materialism as means to understand and transform reality and language as a social practice. The paper conceptualizes what we understand as discourse from a tridimensional viewpoint (social practice, discourse practice and text) and its relations to the concepts of ideology and hegemony. We present the contributions to the pedagogical discourse of Basil Bernstein and Eni Orlandi in order to discuss the specificities of this type of discourse, as well as the use of the notion of merit to justify social relations beneath schooling. At last, we bring some questions over university access in relation to the ideology of merit.